A4.11 Combination of TNF-α and IL-17a promotes osteogenic differentiation, but increases schnurri 3 in isolated human mesenchymal stem cells. (31st January 2014) - Osta, Bilal; Eljaafari, Assia; Lavocat, Fabien; Miossec, Pierre
Abstract : Background and Objectives: Rheumatoid arthritis (RA) is characterised by defective bone repair and excessive bone destruction, and ankylosing spondylitis (AS) by increased ectopic bone formation. Since TNF-α and IL-17A are involved in the pathogenesis of both diseases, the aim of this study was to investigate their effects on the osteogenic differentiation of isolated human bone marrow derived mesenchymal stem cells (hMSCs). Materials and Methods: Differentiation of hMSCs into osteoblasts was induced in the presence or absence of TNF-α and/or IL-17A. Matrix mineralization was evaluated by alizarin red staining and alkaline phosphatase activity measurement. mRNA expression was measured by qRT-PCR for the osteogenesis associated genes BMP2 and RUNX2, for DKK1 the negative regulator of osteogenesis, and for Shn3 and RANKL, genes associated with the cross-talk with osteoclasts. Results: Exposure of isolated hMSCs to TNF-α resulted in a significant acceleration of matrix mineralization, which was potentiated by IL-17A (TNF-α, p = 0.03; TNF-α + IL-17A, p = 0.001 vs. induction medium at day 17). This was associated with a significant increase of alkaline phosphatase activity and an acceleration of its kinetics (TNF-α, p = 0.05; IL-17A, p = 0.01; TNF-α + IL-17A 1, p = 0.01 vs. induction). TNF-α but not IL-17A induced significant a early increase of BMP2 mRNA expression (TNF-α, p = 0.007 vs. induction at 6hrs). The combination of TNF-α and IL-17A induced a strong and sustained significant decrease of DKK1 ( p = 0.03 vs. induction at 72hr) and RANKL ( p = 0.002 vs. induction at 6hr) mRNA expression, but an early significant increase of Schnurri-3 (TNF-α, p = 0.03; TNF-α + IL-17A, p = 0.007 vs. induction at 6hr). On the contrary, Runx2 gene expression was not affected in any conditions. Conclusions: The combined action of TNF-α and IL-17A increased hMSCs osteogenesis, via increasing BMP2 and reducing RANKL and DKK1 gene expression. This could be involved in ectopic bone formation as observed in AS, where osteoclasts are not present. Conversely, increase of Schnurri-3 may activate osteoclasts and bone destruction as observed in RA.